Biosorption study of some heavy metals from its aqueous solutions by plant residue: 1-Adsorpation equilibrium reaction - Hassan, Baidaa Alawi; Jaber, Baidaa Hamid; Yassin, Mohammed Malik (International Journal of Aquatic Research and Environmental Studies, 2025)
Some plant residues (Sidr leaves - Bamber leaves - Palm sap) were used to study their efficiency in the bioabsorption of several heavy metal ions (iron, zinc, and manganese) from solutions contaminated with heavy elements through studying some physicochemical properties and thermal equilibrium reactions in which the thermal equilibrium equation (Langmuir-Frandlage) was tested in the linear form. It was observed that the percentage of heavy elements (iron, zinc, and manganese) adsorption on the surfaces of plant residue particles (Sidr leaves, Bamber leaves, and Palm sap) increased with the decrease in the sizes of these particles, as the percentage of adsorption ranged from less than 100 and 100-200 and 200-300 microns. The highest adsorption percentage was (90.05, 89.61, 89.57, 90.15, 9.68, 89.29, 90.20, 90.06)., 89.87) % of manganese ions on the surfaces of plant residues (Sidr leaves, Bamber leaves, and palm carob) respectively. There was an increase in the adsorbed amount with the increase in the initial concentration added to all elements (iron, zinc, and manganese) and all plant residues (Sidr leaves, Bamber leaves and palm carob), and the highest adsorbed amount was recorded at 52649.62 μg g-1 of manganese on palm carob at the initial concentration of 400 μg ml-1. Most of the elements took the following sequence in increasing adsorption on the surfaces of the adsorption sites: manganese > zinc > iron for all plant residues under study. A decrease was observed in the adsorbed amount of the studied elements per unit mass, as the weight of 1 gram of Sidr leaves gave the lowest adsorbed amount of iron and manganese, amounting to 3081.174 and 4550.667 μg g-1 respectively. The Langmuir equation in its various forms gave the best description of the adsorbed amount through the values of the coefficient of determination R2.
Keywords: Biosorption, Heavy metals, Plant residue, 1-Adsorpation equilibrium reaction